Molecular imaging in oncology - Schober, Otmar; Kießling, Fabian; Debus, Jürgen (Recent Results in Cancer Research, 2020)
Computed tomography and magnetic resonance imaging -- Single photon emission computed tomography – tracer -- Non-peptidyl 18F-labelled PET tracers as radioindicators for the noninvasive detection of cancer -- Ultrasound Imaging -- Optical and opto-acoustic imaging -- Multifunctional magnetic imaging probes -- Modern X-ray concepts-differential phase-contrast imaging -- Pre-clinical SPECT and SPECT-CT -- Optical and photo-acoustic imaging -- Applications of small animal PET -- Preclinical molecular imaging using PET and MRI -- Molecular ultrasound imaging -- Advanced microscopy techniques -- Mass spectroscopy -- Quantitative SPECT-CT -- Optical imaging of breast tumors and of gastrointestinal cancer by laser-induced fluorescence -- FDG PET and PET-CT -- Non-FDG PET-CT -- Clinical MR biomarkers -- Clinical PET-MR -- Advanced ultrasound imaging -- Radiomics and Radiogenomics -- Cross validation techniques -- Image-guided brain surgery -- Image-guided abdominal surgery -- Photon radiation therapy -- Particle radiation therapy -- Internal radiotherapy -- Future challenges of multimodality imaging.